(untitled) (International Journal of Environmental Sciences, 2025)
Introduction: A child is an individual who is a human being between the years of birth and puberty, or between infancy and puberty. Child welfare program seek to provide supportive service to families. Child welfare refers to all the needs of children who are unable to access community services because they are socially, economically, physically, or mentally impaired. Objectives: PRIMARY OBJECTIVES- To assess the effectiveness of structured teaching program on knowledge regarding selected child welfare programs among mothers of under five children in selected area. SECONDARY OBJECTIVES- 1) To assess the pre-test knowledge regarding selected Child Welfare Programs among Mothers of under five children. 2)To assess the post-test knowledge regarding selected Child Welfare Programs among Mothers of under five children. 3) To associate the pre-test and post-test level of knowledge score with selected demographic variables. Methodology: The research design used in this study was Quasi – experimental one group pre- test post-test design to find the effectiveness of structured teaching program on knowledge regarding selected child welfare program among mothers of under five children and also determine to associate the pre-test & post-test knowledge score regarding selected child welfare program among mothers of under five children with their selected demographic variables. Result: Post-test knowledge score of mothers of under five children was higher than pre- test. It shows that 61.18% of the mothers of under five children had very good level of knowledge score and 38.83% of them had excellent level of knowledge score. The mean and standard deviation of the result reveals that mean score is 8.17 and SD is 3.33 in pre- test and mean score is 23.98 and SD is 2.29 in post-study. Conclusion: After the detailed analysis, this study leads to the following conclusion: The mothers of under five children have good and very good level of knowledge regarding selected child welfare programs. There was a significant increase in knowledge of mothers of under five children after introduction of structured teaching program. Association of pre-test was seen with occupation and source of knowledge about child welfare program and association of post- test was seen with age (in years) and monthly family income (Rs.) Thus, it was concluded that structured teaching program on knowledge regarding selected child welfare programs among mothers of under five children in selected areas of the city was found to be effective as a teaching strategy.